Relationship Between Generative Artificial Intelligence Tools and Conceptual Understanding among Undergraduate Students - Shaheen, Farzana; Zafar, Sualeha; Rasheed, Sidra; Farwa, Ume (Pakistan Journal of Humanities and Social Sciences, 2025)
This study aimed to examine the relationship between the use of generative Artificial Intelligence (AI) tools and the conceptual understanding of undergraduate students, and to explore the frequency and purposes of AI tool usage among them. A quantitative correlational design was used, collecting survey data from 298 undergraduate students from two public universities; The Islamia University Bahawalpur and The Govt Sadiq College Women University Bahawalpur, Pakistan. The data covered students’ AI usage patterns and their self-perceived conceptual understanding. Findings showed moderate to high levels of AI tool usage, primarily for academic support, assignment writing, and clarification of complex topics. A significant positive correlation was observed between AI tool usage frequencies and perceived conceptual understanding. While AI tools such as ChatGPT, Claude, and Gemini have potential to enhance learning, the results highlight risks of superficial engagement and overreliance. Structured AI integration policies in higher education are recommended to ensure meaningful and sustainable learning outcomes and guide teachers how to use Artificial Intelligence tools in the classroom to get students more interested and help them remember what they learn.